2015
DOI: 10.5858/arpa.2014-0200-oa
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Advanced-Stage, Metaplastic Breast Carcinoma by Next-Generation Sequencing Reveals Frequent, Targetable Genomic Abnormalities and Potential New Treatment Options

Abstract: Context.-Metastatic metaplastic breast carcinoma (MPBC) is an uncommon, but aggressive, tumor resistant to conventional chemotherapy.Objective.-To learn whether next-generation sequencing could identify potential targets of therapy for patients with relapsed and metastatic MPBC.Design.-Hybridization capture of 3769 exons from 236 cancer-related genes and 47 introns of 19 genes commonly rearranged in cancer was applied to a minimum of 50 ng of DNA extracted from 20 MPBC formalin-fixed, paraffinembedded specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 57 publications
6
58
2
Order By: Relevance
“…5 Potentially targetable mutations identified in our study affected the PIK3CA/Akt/ mTOR signalling pathway (PIK3CA, AKT-1, PTEN) proposing benefits of using PIK3CA and mTOR inhibitors in MBCs. A study of five metastatic MBCs treated with the mTOR inhibitor, temsirolimus in combination with liposomal doxorubicin and bevacizumab showed promising preliminary results.…”
Section: Discussionmentioning
confidence: 78%
“…5 Potentially targetable mutations identified in our study affected the PIK3CA/Akt/ mTOR signalling pathway (PIK3CA, AKT-1, PTEN) proposing benefits of using PIK3CA and mTOR inhibitors in MBCs. A study of five metastatic MBCs treated with the mTOR inhibitor, temsirolimus in combination with liposomal doxorubicin and bevacizumab showed promising preliminary results.…”
Section: Discussionmentioning
confidence: 78%
“…CNVs affect the gene expression patterns by altering the gene dosage in human breast cancer 3234 , hMBCs 7,32 , and breast cancer cell lines 35 . Additionally, specific CNGs are concordant with EMT-related genes up-regulation in multiple human cancer types 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Lessons learned from FBXW7-associated murine cancer models also convincingly demonstrated that it is a bona fide tumor suppressor gene with extensive functions [26]. Recent genetic profiles of human cancers based on high-throughput sequencing revealed that FBXW7 is among the most frequently mutated cancer genes [28][29][30][31][32][33]. Thus, FBXW7 has been illuminated to be a central mediator in tumorigenesis [34].…”
Section: Discussionmentioning
confidence: 97%